Fibrinogen levels and postoperative chest drain blood loss in low-weight (<10 kg) children undergoing cardiac surgery. (November 2019) - Ranucci, Marco; Bianchi, Paolo; Cotza, Mauro; Beccaris, Camilla; Silvetti, Simona; Isgrò, Giuseppe; Giamberti, Alessandro; Baryshnikova, Ekaterina
Introduction: Low-weight (<10 kg) children undergoing cardiac surgery with cardiopulmonary bypass are prone to dilution and consumption of soluble coagulation factors and fibrinogen. Low levels of fibrinogen may represent a possible cause of severe postoperative chest drain blood loss. The present study investigates the association between post–cardiopulmonary bypass fibrinogen levels and postoperative chest drain blood loss and severe bleeding, aiming to identify possible cut-off values to trigger specific interventions. Methods: Prospective cohort study on 77 patients weighing <10 kg undergoing cardiac surgery with cardiopulmonary bypass. Haemostasis and coagulation data were collected before surgery (standard tests and thromboelastometry), after protamine (thromboelastometry) and at the arrival in the intensive care unit (standard tests). The primary outcome variable was severe bleeding (chest drain blood loss >30 ml kg -1 /24h). Results: Factors being independently associated with severe bleeding were the international normalized ratio and the fibrinogen levels at the arrival in the intensive care unit. Once corrected for other confounders, fibrinogen levels had an odds ratio of 0.2 (95% confidence interval = 0.011-0.54) per 1 gL -1 for severe bleeding. The discrimination power was fair (area under the curve = 0.770). The best cut-off value was identified at a fibrinogen level of 150 mg dL -1, with a sensitivity of 52%, a specificity of 85% and a positive predictive value of 60% for severe bleeding. Conclusion: Both a prolonged international normalized ratio and low fibrinogen levels were predictive for severe bleeding, underscoring the role of coagulation factors dilution and consumption in this specific patient population.